Response of sweet corn (Zea mays) to plant population and fertility levels during rabi season* - SAHOO, S C; MAHAPATRA, P K (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted at the Regional Research and Technology Transfer Sub-station, Jashipur in Orissa during rubi (dry) seasons of 2002-03 and 2003-04 to study the effect of plant population of 111.1, 83.3, 66.7 and 55.6 thousand/ha ..........